1992
DOI: 10.7164/antibiotics.45.213
|View full text |Cite
|
Sign up to set email alerts
|

N-Acyl 3-alkylidenyl- and 3-alkyl azetidin-2-ones: A new class of monocyclic .BETA.-lactam antibacterial agents. 1. Structure-activity relationships of 3-isopropylidene and 3-isopropyl analogs.

Abstract: The synthesis and antibacterial activity of a series of 7V-acyl 3-isopropylidenyl-and 3-isopropyl 2-azetidinones having potent in vitro antibacterial activity, particularly against anaerobic organisms, is described. A distinguishing structural feature of these compounds is the lack of any ionizable moiety appendant to the lactam nitrogen. 213In our search for novel synthetic antibacterial agents, we sought to explore the potential utility of a monocyclic /Mactam doubly-activated by an exocyclic C-C double bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…This also explains why the prognostic significance of BCL2 expression depends on the type of cancer. Studies have shown that HPV E6 oncogenic protein is related to a variety of apoptosis regulators, such as BCL2 (48,49). In the unit point analysis of this study, the rs2270115 located in the BCL2 gene did not show a significant association with CC.…”
Section: Discussioncontrasting
confidence: 66%
“…This also explains why the prognostic significance of BCL2 expression depends on the type of cancer. Studies have shown that HPV E6 oncogenic protein is related to a variety of apoptosis regulators, such as BCL2 (48,49). In the unit point analysis of this study, the rs2270115 located in the BCL2 gene did not show a significant association with CC.…”
Section: Discussioncontrasting
confidence: 66%
“…The ZnO nanoparticles also inhibit the growth of bacterium. So, this type of fabric performed good antibacterial activity 51–53…”
Section: Resultsmentioning
confidence: 91%
“…Methyl Pentenoates (3). The compounds labeled as 3 consist of a mixture of methyl pent-3-enoate (mixture of E and Z isomers), methyl pent-4-enoate, and traces of methyl pent-2-enoate.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For example, if R′ = CH 3 , the resulting 4-methoxy-butanoyl- and 5-methoxy-pentanoyl- moieties are fragments of biologically active molecules, such as antibiotics, , prostaglandins and their antagonists, analgesics, bronchodilators, , antiarrhythmics, and flavorings . In addition, alkoxyesters derived by ring-opening of GVL such as the ones depicted in Scheme have stimulated interest as bio-oxygenated solvents; while GVL-derived pentenoates have been considered as synthons for monomers. , …”
Section: Introductionmentioning
confidence: 99%